English Neologisms and Borrowings in Media - Huseynova, Aynura Maharat (Advances in Social Sciences Research Journal, 2022)
This article is divided into two main parts: neologisms and borrowings in media. One of the main features of the modern spoken and written language has been the use of borrowed words, primarily of American-English origin. The lexical environment of a modern person, therefore, contains a significant number of foreign words and neologisms, the use of which seems inevitable for successful communication. Considering the features of the use of borrowings and neologisms in the media is especially significant in modern conditions. The main purpose of this article is to determine the role of its two themes, and to study the features of the translation of neologisms and borrowings from English into Azerbaijani in connection with the constant updating of the English dictionary against the background of the current ever-changing environment.